Breaking the Coupling Efficiency–Bandwidth Trade-Off in Surface Grating Couplers Using Zero-Order Radiation - Sánchez-Postigo, Alejandro; Halir, Robert; Wanguemert-Pérez, Juan Gonzalo; Ortega-Moñux, Alejandro; Wang, Shurui; Vachon, Martin; Schmid, Jens H.; Xu, Dan-Xia; Cheben, Pavel; Molina-Fernández, Íñigo (Wiley, 2021)
Silicon photonics provides wafer-scale fabrication of densely integrated photonic circuits that are enabling breakthrough applications in datacom, artificial intelligence, and healthcare. The sub-micrometer mode size of silicon waveguides makes efficient coupling to conventional single mode fibers extremely challenging. While advanced surface grating couplers can achieve sub-decibel coupling efficiencies, their operation relies on diffraction phenomena, which intrinsically limit the operational bandwidth. Here a novel type of surface coupler is experimentally demonstrated that overcomes the efficiency-bandwidth limitation of conventional diffraction gratings by harnessing zero-order radiation from a subwavelength metamaterial waveguide to a tilted silicon prism. The device achieves a coupling efficiency above 80% to an SMF-28 fiber in a record 1-dB bandwidth beyond 90 nm, opening new venues for highly efficient broadband fiber-to-chip surface coupling in silicon photonics.
Keywords: Circuitos fotónicos; silicon photonics; surface grating couplers; subwavelength grating metamaterials